Some questions arising at criminalistic research of materials, substances and products (Journal of actual problems of jurisprudence, 2019)
In this article the topical issues arising at criminalistic research of materials, substances and products are considered. In a material situation of a scene always there are small and smallest particles and microtraces of various materials and substances which are in a causal relationship with a crime event. Their value as data carriers steadily increased with development of chemical, physical, biological, mathematical methods of the analysis of objects of small weight and especially increased in modern conditions.Key words: microobjects, microtraces, crime event, research of materials, substances and products, chemical analysis, structural analysis.